A Longitudinal Cohort Study of Risk Factors Associated with Small Ruminant Lentivirus Seropositivity in Intensively Reared Dairy Ewes in Greece - Aphrodite I. Kalogianni; Ilias Bouzalas; Ioannis Bossis; Athanasios I. Gelasakis (Pathogens, 2023)
A two-year longitudinal cohort study was conducted on a total of 407 purebred Chios and Lacaune ewes from four intensive dairy sheep farms to assess potential risk factors for small ruminant lentiviruses (SRLVs) seropositivity. Ewes were serologically tested semiannually at pre-mating and pre-lambing, and their age, breed, and body condition score (BCS) were recorded. Εwes were categorized as constantly seronegative, constantly seropositive, seroconverted, seroreverted, or animals with an intermittent presence of antibodies. Mixed binary logistic regression models were used to estimate the adjusted relative risks of the studied risk factors for (i) the individual ewes’ seropositivity, (ii) the manifestation of specific serological patterns, and (iii) the occurrence of seroconversion and seroreversion incidents. Increased age was associated with seropositivity and constantly seropositive status (p < 0.001 in both cases). On the other hand, age was negatively associated with constantly seronegative pattern, seroconversion incident, and the intermittent presence of antibodies (p < 0.05 in all cases). Moreover, breed was recognized as a risk factor: Lacaune ewes demonstrated increased seropositivity, whereas Chios ewes were more likely to demonstrate an intermittent presence of antibodies (p < 0.01 in both cases). Seropositive status (p < 0.001), seropositivity in animals with an intermittent presence of antibodies (p = 0.001), and seroconversion incidents (p < 0.001) were significantly increased at pre-lambing compared to pre-mating. The risk factors recognized in our study contribute to a better understanding of SRLVs epidemiology and the evidence-based designation of SRLVs’ control programs in intensive dairy sheep farms in Greece.